Weakly oxidized graphene preparation method, weakly oxidized graphene and graphene preparation method
Through the weakly oxidized graphene preparation method, the degree of oxidation and the use of corrosion inhibitors are controlled, and the problems of high oxygen content in the existing graphene preparation technology are solved, and graphene preparation with excellent conductivity and low cost are achieved , improving its application potential in industrial production.
Patent Information
- Application Number
- CN202111372508.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-11-18
AI Technical Summary
The existing graphene preparation technology has problems such as high oxygen content leading to reduced conductivity and increased costs, which is difficult to widely use in industrial production.
By using weak graphene oxide preparation method, graphite is pretreated in a mixed atmosphere of argon and oxygen, and corrosion inhibitors with large π conjugated structure are added to control the oxidation degree and reduce the carbon six-membered ring. Destroy and obtain graphene with excellent conductivity through thermal peeling treatment.
It has achieved the preparation of graphene with excellent conductivity and low cost, which is suitable for lithium battery conductive agents, and has improved the application potential of graphene in industrial production.
Smart Images

Figure HDA0003362783990000011 
Figure HDA0003362783990000021 
Figure HDA0003362783990000031
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphene, and in particular to a method for preparing weakly oxidized graphene, weakly oxidized graphene and a method for preparing graphene. Background Art
[0002] Graphene is a new material with a single-layer sheet structure composed of carbon atoms. It is a planar film composed of carbon atoms in a hexagonal honeycomb lattice with sp2 hybrid orbitals. It is a two-dimensional material with a thickness of only one carbon atom. It has many excellent theoretical properties and is widely used in energy storage materials, environmental engineering, and sensitive sensors. It is called "black gold" or "the king of new materials". It has broad potential application prospects and has become the focus of attention and research hotspot around the world.
[0003] At present, the methods for preparing graphene include micromechanical exfoliation, chemical vapor deposition, epitaxial growth, longitudinal cutting of carbon nanotubes and chemical reduction. Among them, the chemical reduction method has the advantages of easy operation, high yield, low cost and large-scale production, and is the method with the most promising industrial application prospects. It is to oxidize graphite to obtain graphene oxide, and then reduce the graphene oxide to obtain graphene. The current reduction methods of graphene oxide are mainly divided into two categories. The first category is reduction by chemical reagents, such as the widely used method of preparing graphene by hydrazine hydrate reduction. Although this method is low in cost, it is highly toxic, and there is a stacking phenomenon between graphene sheets during the reduction process, which is difficult to control; the second category is reduction by heating. This method can directly use graphite oxide as raw material, and quickly heat up and heat to make the graphite oxide interlayer groups overflow violently in large quantities, and stretch the graphite oxide sheets to form graphene.
[0004] In the early stage of graphene development, we mainly studied how to prepare graphene. In more than ten years of development, different types of graphene have emerged. They all have a common feature, the price is only high, and due to the price, the application of graphene is still in its infancy, and there are only a few leading companies that have the strength to carry out industrial applications. Moreover, due to technical limitations, the graphene oxide products commonly available on the market are graphene with high oxygen content and medium flake diameter. Since a large amount of intercalating agents and oxidants are required in the preparation process of graphene with high oxygen content, the relatively violent oxidation and intercalation reactions lead to the destruction of the six-membered ring of graphene, which will affect the conductivity of graphene; on the other hand, the amount of raw materials added will greatly increase the cost of graphene oxide. For example, the relevant patent CN110963488A "A method for preparing small-sized graphene oxide" uses trifluoromethanesulfonic acid and other mixed acids as intercalating agents and reduces them by chemical methods to obtain graphene with better performance. The trifluoromethanesulfonic acid in this method has a high unit price, and the sheet diameter of graphene is 1-20nm. The graphene with nanometer-scale sheet diameter will increase the raw material cost and its output rate is relatively low. Another patent CN105084344A "Method for preparing graphene and graphene prepared by this method" discloses the use of graphite with a small and medium sheet diameter of about 7.5-15μm, oxidation with potassium chlorate, and then stripping treatment. The graphene obtained by this method has a maximum conductivity of 3100S / m, that is, a resistivity of about 32mΩ.cm, and general conductivity. For CN108928815B "A method for preparing high-performance graphene using a multi-step weak oxidation-reduction method", a method of using a weak oxidant instead of a strong oxidant, using a mixed solution of an organic carboxylic acid solution and a weak oxidant solution to immerse flake graphite in a closed state at room temperature is disclosed. Although it protects the environment and saves costs, it greatly prolongs the preparation time and is actually not suitable for industrial production. Due to current technical limitations, the price of graphene with good performance on the market is very expensive, making it difficult to be widely used in industrial production. With the continuous improvement of technology, how to prepare graphene with low cost and good conductivity has become the direction of development, so further improvement is urgently needed. Summary of the invention
[0005] In order to obtain graphene with low cost and good conductivity, the present application provides a method for preparing weakly oxidized graphene and a method for preparing weakly oxidized graphene and graphene.
[0006] In a first aspect, the present application provides a method for preparing weakly oxidized graphene.
[0007] Step 1: Treat graphite in a mixed atmosphere of argon and oxygen for 1-3 hours at a temperature of 300-500°C and a pressure of less than 5 Pa to obtain pretreated graphite; wherein the flow ratio of argon to oxygen is (25-500):1.
[0008] Step 2: Then, add the corrosion inhibitor to the pretreated graphite and stir evenly to form a graphite mixture. Mix the graphite mixture with the intercalation agent, stir and perform an intercalation reaction at 5-15° C. to form an intermediate product.
[0009] Step 3: Mix the intermediate product with an oxidant, react at a temperature of 10-15°C for 1-3h, add water and raise the temperature to 40-60°C to continue the reaction for 1-2h, then add hydrogen peroxide to terminate the reaction, filter, wash to a pH of 6-7, and then dry to obtain weakly oxidized graphene;
[0010] The corrosion inhibitor is an organic acid with a large π conjugated structure and an acidity coefficient PKa value of 3-5;
[0011] The mass ratio of the pretreated graphite to the corrosion inhibitor is (25-50):1.
[0012] Through the above technical scheme, the graphite is first pre-oxidized to improve the wettability of the subsequent graphite and the efficiency of the intercalation reaction, and then a corrosion inhibitor with a large π conjugated structure is further added to protect the graphene surface, reduce the degree of destruction of the carbon hexagonal ring during the reaction process, and also reduce the formation of holes on the graphene surface that will destroy the graphene structure and excessive oxidation, while reducing the introduction of invalid oxygen functional groups, thereby obtaining weakly oxidized graphene with a sheet thickness of 1-3nm and an oxygen content of 25-35%.
[0013] Compared with the graphene with high oxygen content and medium sheet diameter in the prior art, since the graphene with high oxygen content needs to use a large amount of intercalating agent and oxidant in the preparation process, it will lead to relatively violent oxidation and intercalation reaction, resulting in the destruction of the graphene six-membered ring, affecting the subsequent conductivity, and the cost is greatly increased. The present application pre-oxidizes the flake graphite with small and medium sheet diameters under weak oxygen to improve the subsequent wettability of graphite and the efficiency of intercalation reaction, and then adds a corrosion inhibitor with a large π conjugated structure to protect the oxidized graphene, reduce the destruction of the carbon six-membered ring during the reaction, and then undergoes subsequent reduction treatment. The organic acid used is cheap and easy to obtain, and finally obtains graphene with excellent conductivity and low cost that can be used in lithium battery conductive agents.
[0014] Preferably, the corrosion inhibitor is one or a mixture of benzoic acid, rhein, pyrenecarboxylic acid, pyrenebutyric acid, and phenanthroic acid, and the mass ratio of the pretreated graphite to the corrosion inhibitor is (30-45):1.
[0015] Under the action of the above-mentioned low-cost corrosion inhibitor, the carbon hexagonal ring of graphene oxide is further protected, the structure of weak graphene oxide is more complete, and the layer structure in the subsequent thermal stripping process is more complete, thereby obtaining graphene with better conductive properties.
[0016] Preferably, the intercalant is one or a mixture of concentrated sulfuric acid, perchloric acid, nitric acid, acetic acid and phosphoric acid; the ratio of the intercalant to the pretreated graphite is (25-40):1.
[0017] By further limiting the type and addition amount of the intercalating agent and coordinating it with the corrosion inhibitor, the structure of the graphite flakes formed is more complete, and the structure of the graphene prepared subsequently is more complete, thereby further improving the conductive properties of the graphene. At the same time, the above-mentioned intercalating agent is a commonly used and low-cost acid in industry, which further reduces the cost of preparing graphene.
[0018] Preferably, the oxidant is potassium permanganate, hydrogen peroxide, potassium dichromate, potassium ferrate, sodium ferrate or a mixture thereof, and the ratio of the oxidant to the pretreated graphite is (0.8-2):1.
[0019] By using the above-mentioned proportion and limited types of oxidants, the pretreated graphene treated with the above-mentioned corrosion inhibitor and intercalant is more fully oxidized, the exfoliation is more thorough in the subsequent preparation of graphene, the overlap between graphene sheets is reduced, the specific surface area of graphene is not easily affected and becomes larger, thereby further increasing the conductivity of the finally prepared graphene.
[0020] Preferably, the flake diameter of the graphite is 10-35 μm, and the carbon content of the graphite is greater than 95%, and is further preferably 10-25 μm.
[0021] The use of graphite raw materials with small and medium flake diameters has lower raw material costs than the existing cost of using small flake diameters to obtain graphene with better performance, and shortens the diffusion path of the intercalant and oxidant into the graphite flakes, so that the edges and interior of the graphite are evenly oxidized, thereby obtaining relatively thin graphene with better conductivity.
[0022] The pretreatment device in step 1 is a rotary kiln, and the rotation speed of the rotary kiln is 0.5-2r / min.
[0023] In the present application, graphene oxide is prepared by introducing trace oxygen through a carrier gas under the action of a rotary kiln, and the trace oxygen is evenly diffused and reacted on the surface of the graphite raw material and in the flakes, and the diffusion rate is further accelerated, thereby further improving the wettability of the graphite surface and the efficiency of the intercalation reaction, thereby obtaining graphene with better conductivity.
[0024] In a second aspect, the present application provides a weakly oxidized graphene, wherein the weakly oxidized graphene is a few-layer graphene oxide with a thickness of 1-3 nm, and the oxygen content of the weakly oxidized graphene is 25%-35%.
[0025] In a third aspect, the present application provides a method for preparing graphene, wherein the weakly oxidized graphene obtained by the above method is subjected to a thermal stripping treatment for 100-600 seconds at a temperature of 800°C-1000°C, and a gas flow ratio of the inert gas to the reducing gas is (10-100):1.
[0026] By reducing the gas and heating it to above 800°C, the functional groups and intercalants on the surface of the weakly oxidized graphene decompose and release gases to expand the interlayer spacing, thereby achieving the purpose of reducing the weakly oxidized graphene. In this process, most of the oxygen-containing groups are removed. After the above treatment, the highly oxidized graphene is difficult to disperse, which limits its handling and compatibility. Compared with the graphene prepared from the existing highly oxidized graphene, the graphene prepared in this application has excellent dispersibility and compatibility, with a specific surface area of 200-400 m 2 / g, can be applied to conductive materials and has very high electrical conductivity.
[0027] Preferably, the inert gas is argon, the reducing gas is hydrogen, and the gas flow ratio of the inert gas to the reducing gas is (20-60):1.
[0028] During the thermal stripping process, argon is used as a protective gas and a reducing gas in the above-mentioned gas flow ratio, which not only provides a safe reaction environment, but also plays a role in repairing the defects of the sheet after stripping, thereby increasing the conductivity of graphene.
[0029] Preferably, the graphene oxide is thermally exfoliated in a tubular furnace or an expansion furnace.
[0030] Further limiting the gas flow ratio of the inert gas to the reducing gas and restricting the equipment used further expands the interlayer spacing of the graphene, removes the oxygen-containing groups more thoroughly, and further improves the conductivity of the resulting graphene.
[0031] Beneficial effects: The present application adopts a corrosion inhibitor and graphite in a mass ratio of 1: (25-50), and the corrosion inhibitor is an organic acid with a large π conjugated structure and an acidity coefficient PKa value of 3-5, which protects the surface of graphene, reduces the degree of destruction of the carbon hexagonal ring during the reaction process, and also reduces the formation of holes on the graphene surface that will destroy the graphene structure and excessive oxidation, while reducing the introduction of invalid oxygen functional groups, thereby obtaining weakly oxidized graphene with a sheet thickness of 1-3nm and an oxygen content of 25-35%, and then undergoes subsequent reduction treatment to finally obtain graphene with excellent conductive properties and low cost that can be used in lithium battery conductive agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 (a) and Figure 1(b) is a SEM scanning electron microscope image used to show the diameter of the weakly oxidized graphene sheet in Preparation Example 1.
[0033] Figure 1 (c) is a TEM image used to show the number of weakly oxidized graphene layers in Preparation Example 1.
[0034] Figure 1 (d) is a Raman spectrum diagram used to represent the molecular structure of weakly oxidized graphene in Preparation Example 1.
[0035] Figure 1 (e) and Figure 1 (f) is an AFM image used to show the thickness of the weakly oxidized graphene sheet in Preparation Example 1.
[0036] Figure 2 (a) and 2 (b) are SEM images used to show the diameter of weakly oxidized graphene sheets in Preparation Example 2.
[0037] Figure 2 (c) is a TEM image used to show the number of weakly oxidized graphene layers in Preparation Example 2.
[0038] Figure 2 (d) is a Raman spectrum diagram used to represent the molecular structure of weakly oxidized graphene in Preparation Example 2.
[0039] Figure 2 (e) and Figure 2 (f) is an AFM image used to show the thickness of the weakly oxidized graphene sheet in Preparation Example 2.
[0040] Figure 3 (a) and Figure 3 (b) is a SEM scanning electron microscope image used to show the diameter of the weakly oxidized graphene sheet in Preparation Example 3.
[0041] Figure 3 (c) is a TEM image used to show the number of weakly oxidized graphene layers in Preparation Example 3.
[0042] Figure 3 (d) is a Raman spectrum diagram used to represent the molecular structure of weakly oxidized graphene in Preparation Example 3.
[0043] Figure 3 (e) and Figure 3 (f) is an AFM image used to show the thickness of the weakly oxidized graphene sheet in Preparation Example 3. DETAILED DESCRIPTION
[0044] Preparation Example
[0045] Preparation Example 1
[0046] This preparation example discloses a weakly oxidized graphene, which is prepared by the following steps:
[0047] Step 1: Take 2 kg of graphite with a sheet diameter of 30 μm and put it into a rotary kiln for pretreatment. The rotary kiln temperature is 450°C, the rotation speed is 1 r / min, the argon flow rate is 500 sccm, the oxygen flow rate is 2.5 sccm; the equipment pressure is 2.3 Pa, and the treatment time is 1.2 h to obtain pretreated graphite.
[0048] Step 2:
[0049] 20 grams of pretreated graphite was mixed with 0.6 grams of benzoic acid powder for 30 minutes to obtain a graphite mixture.
[0050] The mixture was added to 800 g of 98% concentrated sulfuric acid intercalant. The stirrer was turned on for stirring at a speed of 150 r / min. The temperature control device was turned on to control the reaction temperature at 10° C. The reaction time was 1 h to obtain an intermediate product.
[0051] Step 3: Add 40 grams of potassium permanganate, an oxidant, to the first phase intermediate product at a temperature of 10°C, and continue stirring the reaction for 2 hours. After the reaction is completed, add 400 grams of water, control the temperature at 55°C for a medium-temperature reaction, and the medium-temperature reaction time is 2 hours. After the reaction is completed, add 40 grams of hydrogen peroxide to end the reaction. Filter the sample, wash it with water to pH 6-7, and then dry it to obtain weakly oxidized graphene with a sheet size of 25μm and an oxygen content of 34%.
[0052] The mass ratio of the corrosion inhibitor to the pretreated graphite is 1:33, the ratio of the intercalating agent to the pretreated graphite is 40:1, and the ratio of the oxidant to the pretreated graphite is 2:1.
[0053] according to Figure 1 (a) and Figure 1 (b) It can be seen that the morphology of the graphene oxide in Preparation Example 1 is orderly multi-layer wrinkles, indicating that the surface structure of the graphene oxide is relatively intact.
[0054] according to Figure 1 (c) It can be seen that the weakly oxidized graphene of Preparation Example 1 is 9-layer graphene oxide.
[0055] according to Figure 1 (d) It can be seen that IG / ID=1.21, indicating that the obtained graphene oxide has few defects and good quality.
[0056] according to Figure 1 (e) and Figure 1 (f) It can be seen that the sheet thickness of the weakly oxidized graphene in Preparation Example 1 is 1.92 nm.
[0057] Preparation Example 2
[0058] This preparation example discloses a weakly oxidized graphene, which is prepared by the following steps:
[0059] Step 1: Take 2 kg of graphite with a sheet diameter of 25 μm and put it into a rotary kiln for pretreatment. The rotary kiln temperature is 400°C, the rotation speed is 1 r / min, the argon flow rate is 500 sccm, the oxygen flow rate is 2.5 sccm; the equipment pressure is 2.3 Pa, and the treatment time is 1 hour to obtain pretreated graphite.
[0060] Step 2: Take 20 grams of pretreated graphite and mix it with 0.8 grams of pyrenebutyric acid powder for 30 minutes to obtain a graphite mixture.
[0061] The mixture was added to 600 g of 98% concentrated sulfuric acid intercalant. The stirrer was turned on for stirring at a speed of 150 r / min, and the temperature control device was turned on to control the reaction temperature at 10° C. The reaction time was 1 h to obtain an intermediate product.
[0062] Step 3: Add 20 grams of potassium dichromate, an oxidant, to the first phase intermediate product at a temperature of 10°C, and continue stirring and reacting for 1.5 hours. After the reaction is completed, add 300 grams of water, control the temperature at 50°C for medium-temperature reaction, and the medium-temperature reaction time is 2 hours. After the reaction is completed, add 35 grams of hydrogen peroxide to end the reaction. Filter the sample, wash it with water to pH 6-7, and then dry it to obtain weakly oxidized graphene with a sheet size of 20μm and an oxygen content of 28%.
[0063] The mass ratio of the corrosion inhibitor to the pretreated graphite is 1:25, the ratio of the intercalating agent to the pretreated graphite is 30:1, and the ratio of the oxidant to the pretreated graphite is 1:1.
[0064] according to Figure 2 (a) and Figure 2 (b) It can be seen that the morphology of the graphene oxide in Preparation Example 2 is similar to that in Preparation Example 1, showing ordered multi-layer wrinkles, indicating that the surface structure of the graphene oxide is relatively intact.
[0065] according to Figure 2 (c) It can be seen that the weakly oxidized graphene of Preparation Example 2 is 6-7 layers of graphene oxide.
[0066] according to Figure 2 (d) It can be seen that IG / ID=1.16, and the quality of graphene oxide is good.
[0067] according to Figure 2 (e) and Figure 2 (f) It can be seen that the sheet thickness of the weakly oxidized graphene in Preparation Example 2 is 2.66 nm.
[0068] Preparation Example 3
[0069] This preparation example discloses a weakly oxidized graphene, which is prepared by the following steps:
[0070] Step 1: Take 2 kg of graphite with a sheet diameter of 15 μm and put it into a rotary kiln for pretreatment. The rotary kiln temperature is 400°C, the rotation speed is 1 r / min, the argon flow rate is 500 sccm, the oxygen flow rate is 2.5 sccm, the equipment pressure is 2.3 Pa, and the treatment time is 1 hour to obtain pretreated graphite.
[0071] Step 2: Take 20 grams of pretreated graphite and mix it with 0.45 grams of phenacic acid powder for 30 minutes to obtain a graphite mixture.
[0072] The mixture was added to 500 g of 98% concentrated sulfuric acid and 100 g of 85% by mass phosphoric acid mixed acid intercalation agent. The stirrer was turned on for stirring at a stirring speed of 150 r / min, and the temperature control device was turned on to control the reaction temperature at 10°C. The reaction time was 1 h to obtain an intermediate product.
[0073] Step 3: Add 24 grams of potassium permanganate, an oxidant, to the first phase intermediate product at a temperature of 10°C, and continue stirring the reaction for 2 hours. After the reaction is completed, add 400 grams of water, control the temperature at 55°C for a medium-temperature reaction, and the medium-temperature reaction time is 2 hours. After the reaction is completed, add 30 grams of hydrogen peroxide to end the reaction. Filter the sample, wash it with water to a pH of 6-7, and then dry it to obtain weakly oxidized graphene with a sheet size of 13μm and an oxygen content of 30%.
[0074] The mass ratio of the corrosion inhibitor to the pretreated graphite is 1:44, the ratio of the intercalating agent to the pretreated graphite is 25:1, and the ratio of the oxidant to the pretreated graphite is 1.2:1.
[0075] according to Figure 3 (a) and Figure 3 (b) It can be seen that the morphology of the graphene oxide in Preparation Example 3 is similar to that in Preparation Example 1, showing ordered multi-layer wrinkles, indicating that the surface structure of the graphene oxide is relatively intact.
[0076] according to Figure 3 (c) It can be seen that the weakly oxidized graphene of Preparation Example 3 is 6-7 layers of graphene oxide.
[0077] according to Figure 3 (d) It can be seen that IG / ID=1.13, and the quality of graphene oxide is good.
[0078] according to Figure 3 (e) and Figure 3 (f) It can be seen that the sheet thickness of the weakly oxidized graphene in Preparation Example 3 is 2.29 nm.
[0079] Preparation Example 4
[0080] This preparation example discloses a weakly oxidized graphene, which is prepared by the following steps:
[0081] Step 1: Take 2 kg of graphite with a sheet diameter of 10 μm and put it into a rotary kiln for pretreatment. The rotary kiln temperature is 300°C, the rotation speed is 0.5 r / min, the argon flow rate is 500 sccm, the oxygen flow rate is 20 sccm, the equipment pressure is 1 Pa, and the treatment time is 1 hour to obtain pretreated graphite.
[0082] Step 2: Take 20 grams of pretreated graphite and mix it with 0.5 grams of rhein powder for 30 minutes to obtain a graphite mixture, add the mixture into 400 grams of 98% concentrated sulfuric acid intercalation agent, turn on the stirrer for stirring, the stirring speed is 150r / min, turn on the temperature control device to control the reaction temperature at 5°C, the reaction time is 3 hours, and obtain an intermediate product.
[0083] Step 3: Add 20g of potassium permanganate, an oxidant, to the intermediate product at a temperature of 10°C, and continue stirring the reaction for 3h. After the reaction is completed, add 400g of water, control the temperature at 40°C for a medium-temperature reaction, and the medium-temperature reaction time is 2h. After the reaction is completed, add 25g of hydrogen peroxide to terminate the reaction. Filter the sample, wash it with water to a pH of 6-7, and then dry it to obtain a weakly oxidized graphene with a sheet size of 10μm, a sheet thickness of 2.72nm, and an oxygen content of 27.2%.
[0084] The ratio of intercalating agent to pretreated graphite is 20:1, and the ratio of oxidizing agent to pretreated graphite is 1:1.
[0085] Preparation Example 5
[0086] This preparation example discloses a weakly oxidized graphene, which is prepared by the following steps:
[0087] Step 1: Take 2 kg of graphite with a sheet diameter of 35 μm and put it into a rotary kiln for pretreatment. The rotary kiln temperature is 500°C, the rotation speed is 2 r / min, the argon flow rate is 500 sccm, the oxygen flow rate is 1 sccm, the equipment pressure is 5 Pa, and the treatment time is 3 hours to obtain pretreated graphite.
[0088] Step 2: Take 20 grams of pretreated graphite and mix it with 0.6 grams of benzoic acid powder for 30 minutes to obtain a graphite mixture, add the mixture into 1000 grams of 98% concentrated sulfuric acid as an intercalation agent, turn on the stirrer for stirring, the stirring speed is 150r / min, turn on the temperature control device to control the reaction temperature at 15°C, the reaction time is 1h, and an intermediate product is obtained.
[0089] Step 3: Add 16g of potassium permanganate, an oxidant, to the intermediate product at a temperature of 15°C, and continue stirring the reaction for 1h. After the reaction is completed, add 400g of water, control the temperature at 60°C for a medium-temperature reaction, and the medium-temperature reaction time is 1h. After the reaction is completed, add 45g of hydrogen peroxide to terminate the reaction. Filter the sample, wash it with water to a pH of 6-7, and then dry it to obtain a weakly oxidized graphene with a sheet size of 32μm, a sheet thickness of 2.86nm, and an oxygen content of 26.8%.
[0090] The mass ratio of pretreated graphite to corrosion inhibitor is 50:1, the ratio of pretreated graphite to intercalation agent is 50:1, and the ratio of oxidant to pretreated graphite is 0.8:1.
[0091] Preparation Example 6
[0092] The difference from Preparation Example 1 is that the corrosion inhibitor is compounded by 0.3 g of benzoic acid and 0.3 g of pyrenecarboxylic acid, and weakly oxidized graphene with a flake size of 24 μm, a flake thickness of 1.94 nm, and an oxygen content of 33.6% is obtained.
[0093] Preparation Example 7
[0094] The difference from Preparation Example 1 is that the intercalant is compounded by 300 g of 70% perchloric acid and 500 g of 85% phosphoric acid, and a weakly oxidized graphene with a sheet size of 23 μm, a sheet thickness of 2.23 nm, and an oxygen content of 32.8% is obtained.
[0095] Preparation Example 8
[0096] The difference from Preparation Example 1 is that the oxidant is compounded by 30 g of 30% by mass hydrogen peroxide and 10 g of potassium ferrate, and weakly oxidized graphene with a flake size of 24 μm, a flake thickness of 2.03 nm, and an oxygen content of 32.0% is obtained.
[0097] Preparation Example 9
[0098] The difference from Preparation Example 8 is that the oxidant is compounded by 25g of hydrogen peroxide, 5g of potassium ferrate and 10g of sodium ferrate, and the obtained weakly oxidized graphene has a sheet size of 24μm, a sheet thickness of 1.72nm and an oxygen content of 34.2%. Example
[0099] Example 1
[0100] The present embodiment discloses a method for preparing graphene, specifically, the weakly oxidized graphene obtained in Preparation Example 1 is crushed, and then put into a tube furnace for medium temperature thermal exfoliation treatment, the treatment temperature is 800°C, the time is 500s, the protective atmosphere argon flow rate is 800sccm / min; the hydrogen flow rate is 20sccm / min, and the graphene is obtained after the material is collected. The specific surface area of the graphene obtained after the material is collected is 380m 2 / g, powder resistivity is 5.62mΩ.cm.
[0101] Example 2
[0102] This embodiment discloses a method for preparing graphene, specifically, the weakly oxidized graphene obtained in Preparation Example 2 is crushed, and then put into a puffing furnace for medium temperature thermal exfoliation treatment, the treatment temperature is 850°C, the time is 250s, the protective atmosphere argon flow rate is 800sccm / min, the hydrogen flow rate is 20sccm / min, and the specific surface area of the graphene obtained after the material is collected is 270m 2 / g, and the powder resistivity is 13.58mΩ.cm.
[0103] Example 3
[0104] This embodiment discloses a method for preparing graphene, specifically: the weakly oxidized graphene obtained in Preparation Example 2 is crushed, and then put into a tube furnace for medium-temperature thermal exfoliation treatment, the treatment temperature is 1000°C, the time is 100s, the protective atmosphere argon flow rate is 600sccm / min, the hydrogen flow rate is 30sccm / min, and the specific surface area of the graphene obtained after the material is collected is 330m 2 / g, powder resistivity is 7.28mΩ.cm.
[0105] Embodiment 4-9
[0106] The difference from Example 1 is that the weakly oxidized graphene used in Examples 4-9 is the weakly oxidized graphene prepared in Preparation Examples 4-9, respectively, and the specific surface area and powder resistivity are summarized in Table 1 below.
[0107] Example 10
[0108] This embodiment discloses a method for preparing graphene, which is different from the first embodiment in that the gas flow ratio of the inert gas and the reducing gas is 20:1, that is, the protective atmosphere argon flow rate is 1000 sccm / min, the hydrogen flow rate is 50 sccm / min, and the specific surface area of the obtained graphene is 320 m 2 / g, powder resistivity is 7.67mΩ.cm.
[0109] Embodiment 11
[0110] This embodiment discloses a method for preparing graphene, which is different from the first embodiment in that the gas flow ratio of the inert gas and the reducing gas is 60:1, that is, the protective atmosphere argon flow rate is 1000 sccm / min, the hydrogen flow rate is 16.7 sccm / min, and the specific surface area of the obtained graphene is 240 m 2 / g, powder resistivity is 11.12mΩ.cm.
[0111] Comparative Example
[0112] Comparative Example 1
[0113] This comparative example discloses a method for preparing graphene using chlorosulfonic acid.
[0114] Weigh 0.6 g of 19 μm graphite powder and place it in a 50 ml reactor, add 6 ml of chlorosulfonic acid and mix, and place the mixture in a polytetrafluoroethylene reactor at 120°C and heat for 5 hours to obtain pretreated graphite. Subsequently, take out the pretreated graphite and add 15 ml of concentrated sulfuric acid, add 6 ml of hydrogen peroxide solution dropwise under stirring to expand the pretreated graphite, and react for 10 minutes to obtain pretreated expanded graphite. Add water to the pretreated expanded graphite to separate the pretreated expanded graphite from the solution, and filter and wash the obtained expanded graphite product, and then dry to obtain expanded graphite.
[0115] Take 50 mg of the expanded graphite, mix it with potassium chlorate in a ratio of 1:3, and add 12 ml of a mixed solution of concentrated sulfuric acid and nitric acid (the ratio of concentrated sulfuric acid to nitric acid in the mixed solution is 3:1), and then place it for reaction. After 2 days of reaction, the obtained product is centrifuged to obtain expanded graphite with partial oxidation on the surface, or the obtained product is filtered and dried to obtain expanded graphite with partial oxidation on the surface. The partially oxidized expanded graphite on the surface is dispersed ultrasonically (power 100 W, duration 0.5 h) in N-methylpyrrolidone to obtain a graphene suspension, and graphene with a conductivity of 2320 S / m, that is, a resistivity of 43.1 mΩ.cm, is obtained.
[0116] Table 1
[0117] Example <![CDATA[Specific surface area m 2 / g]]> Powder resistivity / mΩ.cm Example 1 380 5.62 Example 2 270 13.58 Example 3 330 7.28 Example 4 265 13.63 Example 5 253 13.92 Example 6 374 5.71 Example 7 340 5.68 Example 8 365 5.89 Example 9 400 4.83 Example 10 320 7.67 Embodiment 11 240 11.12 Comparative Example 1 - 43.1
[0118] According to the comparison between comparative example 1 and examples 1-11 in Table 1, compared with the technical solution of using expensive raw material chlorosulfonic acid to prepare graphene with high resistivity in the prior art, the present application uses a corrosion inhibitor and graphite with a mass ratio of 1: (25-50), and the corrosion inhibitor is an organic acid with a large π conjugated structure and an acidity coefficient PKa value of 3-5 to finally prepare the graphene, and obtain graphene with a resistivity as low as 4.83 / mΩ.cm. Not only does it have excellent conductive properties, but it also has low processing costs, providing new ideas for the application of graphene in industrial production.
[0119] According to the data comparison of Examples 1-4 in Table 1, it can be seen that the mass ratio of pretreated graphite to corrosion inhibitor in Examples 1 and 3 is in the range of (30-45):1, while that in Examples 2 and 4 is (25-50):1. The resistivity of Examples 1 and 3 is less than that of Examples 2 and 4, indicating that the mass ratio of pretreated graphite to corrosion inhibitor is controlled within the range of (30-45):1, which can further improve the conductive properties of graphene.
[0120] According to the data comparison of Examples 1 and 3 with Examples 4 and 5, it can be obtained that the mass ratio of the intercalant to the pretreated graphite of Examples 1 and 3 is in the range of (25-40):1, and that of Examples 4 and 5 is in the range of (20-50):1. The resistivity of Examples 1 and 3 is less than that of Examples 4 and 5, indicating that controlling the mass ratio of the intercalant to the pretreated graphite in the range of (25-40):1 can further improve the electrical properties of graphene.
[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A method for preparing weakly oxidized graphene, characterized in that: The following steps are included: Step 1: treating graphite in a mixed atmosphere of argon and oxygen for 1-3 hours at a temperature of 300-500°C and a pressure of less than 5 Pa to obtain pretreated graphite; wherein the flow ratio of argon to oxygen is (25-500):1; Step 2: adding a corrosion inhibitor to the pretreated graphite and stirring evenly to form a graphite mixture; mixing the graphite mixture with an intercalation agent, stirring and performing an intercalation reaction at 5-15° C. to form an intermediate product; Step 3: Mix the intermediate product with an oxidant, react at a temperature of 10-15°C for 1-3h, add water and raise the temperature to 40-60°C to continue the reaction for 1-2h, then add hydrogen peroxide to terminate the reaction, filter, wash to a pH of 6-7, and then dry to obtain weakly oxidized graphene; The corrosion inhibitor is an organic acid with a large π conjugated structure and an acidity coefficient PKa value of 3-5; The mass ratio of the pretreated graphite to the corrosion inhibitor is (25-50):
1.
2. A method for preparing weakly oxidized graphene according to claim 1, characterized in that: The corrosion inhibitor is one or a mixture of benzoic acid, rhein, pyrenecarboxylic acid, pyrenebutyric acid, and phenanthroic acid, and the mass ratio of the pretreated graphite to the corrosion inhibitor is (30-45):
1.
3. A method for preparing weakly oxidized graphene according to any one of claims 1 or 2, characterized in that: The intercalation agent is one or a mixture of concentrated sulfuric acid, perchloric acid, nitric acid, acetic acid and phosphoric acid; the mass ratio of the intercalation agent to the pretreated graphite is (25-40):
1.
4. The method for preparing weakly oxidized graphene according to any one of claims 1 or 2, characterized in that: The oxidant is one or a mixture of potassium permanganate, hydrogen peroxide, potassium dichromate, potassium ferrate, sodium ferrate; the mass ratio of the oxidant to the pretreated graphite is (0.8-2):
1.
5. The method for preparing weakly oxidized graphene according to any one of claims 1 or 2, characterized in that: The flake diameter of the graphite is 10-35 μm, and the carbon content of the graphite is greater than 95%.
6. The method for preparing weakly oxidized graphene according to any one of claims 1 or 2, characterized in that: The pretreatment device in step 1 is a rotary kiln, and the rotation speed of the rotary kiln is 0.5-2r / min.
7. A weakly oxidized graphene, characterized in that: The weakly oxidized graphene is prepared according to the preparation method of any one of claims 1 to 6, wherein the weakly oxidized graphene is a few-layer oxidized graphene with a thickness of 1 to 3 nm, and the oxygen content of the weakly oxidized graphene is 25% to 35%.
8. A method for preparing graphene, characterized in that: The weakly oxidized graphene according to claim 7 is subjected to a thermal stripping treatment at a temperature of 800° C. to 1000° C. for 100 to 600 seconds, wherein the gas flow ratio of the inert gas to the reducing gas is (10-100):
1.
9. The method for preparing graphene according to claim 8, characterized in that: The inert gas is argon, the reducing gas is hydrogen, and the gas flow ratio of the inert gas to the reducing gas is (20-60):
1.
10. The method for preparing graphene according to claim 8 or 9, characterized in that: The weakly oxidized graphene is subjected to thermal exfoliation treatment in a tube furnace or an expansion furnace.
Citation Information
Patent Citations
Graphene preparation method and graphene prepared through graphene preparation method
CN105084344A
A method for preparing high-performance graphene using a multi-step weak oxidation-reduction method
CN108928815B
Low-cost mass preparation method of high-quality graphene
CN103382026A
Method for large-scale preparation of bulky graphene
CN104386680A